The Rationality Of The Judge's Decision States That Good Faith Is The Basis For Canceling The Lease Agreement For Land And Buildings Under His Control - Desy Nur Aini, Fajar; Karjoko, Lego; Tuhana, Tuhana (CV. Inara, 2024)
In general, when people make written agreements regarding the rental of land and house buildings, they are usually made privately, some of which are notarized (Notarial Deeds), some parties choose to make written agreements regarding the rental of land and house buildings. made by hand with sufficient stamp duty. One example of the Supreme Court Decision Number 1078 K/Pdt/2021, the basis of the lawsuit filed by the Plaintiff is Bad Faith committed by the owner of the rental object in the lease extension agreement for the land and building under his control, then the actions or actions of the owner of the leased object can be categorized as an act of breach of contract or breach of contract. This research aims to find out whether there is a rational basis for the judge's decision which states good faith as a basis for canceling land and building lease agreements based on Supreme Court Decision Number 1078 K/Pdt/2021. This research method uses normative juridical research using a case approach. The analysis technique used is the syllogism method and interpretation using deductive thinking patterns. The results of the research and discussion can be concluded that legal rationality is needed by judges in carrying out their considerations in order to determine decisions that contain the values ​​of justice and the law that applies in Indonesia. This does not only apply to one type of legal rationality but also applies to other types. The use of this type of legal rationality requires looking at the relationship between facts, norms, morals and doctrine in considering the judge's decision. The issue of default used in the main issue in the decision becomes a boomerang for the tenant, in this case the tenant, because there is no legal force in the rental agreement signed by the tenant with the renting party. Different conditions will occur if the rental agreement is made before a notary and explains that they have entered into an agreement and asks the Notary to make a deed, then this deed is a deed made before a Notary (Notarial Deed). So in this case, the parties to the agreement have legal certainty and are therefore legally protected, so that if a dispute occurs in the implementation of the agreement, the judge with his decision can force the violating party to carry out its rights and obligations according to the agreement.